How to Measure Body Condition Score in Florida Beef Cattle - Matthew J. Hersom; Todd A. Thrift (EDIS)
Body condition score (BCS) is both a good indicator of the past nutritional status of a cow and a way to determine future nutritional needs. The BCS technique is easy to learn and can help with management decisions. This new 5-page fact sheet discusses reasons to measure BCS, ways to evaluate BCS, and important assessment times. Written by Matt Hersom and Todd Thrift, and published by the UF/IFAS Department of Animal Sciences, August 2018. http://edis.ifas.ufl.edu/an347